Local Well-posedness and Blow Up Criterion for the Inviscid Boussinesq System in Hölder Spaces (Journal of Partial Differential Equations, 2012)
We prove the local in time existence and a blow up criterion of solution in the Hölder spaces for the inviscid Boussinesq system in R^N, N≥ 2, under the assumptions that the initial values θ_0, μ_0∈C^r, with 1< r≠ 2.
Keywords: Inviscid Boussinesq system; local well-posedness; blow-up criterion